Simple dynamic model of predicting the axle-box acceleration when trains pass through the rupture part of rails - Hiroyuki AIZAWA; Mitsuru HOSODA; Ryuichi YAMAMOTO (Nihon Kikai Gakkai ronbunshu, 2021)
In this paper, the simple dynamic model for calculation of the axle-box acceleration (ABA) is established for conveniently detecting rail breakage on trains. Track circuit based signaling system, whose functions are detection of vehicles and rail breakage, is tend to be replaced by Communication Based Train Control system because it is expected to reduce the cost for maintaining equipment along railways. In order to maximize the advantage of reduction in costs, the way to detect rail breakage on the vehicles should also be established. The running tests on the rupture part of rails on a ballasted track and a ballasted ladder track are conducted, and the ABAs obtained in each test are analyzed. The dynamic models corresponding to two types of tracks consist of beams on elastic foundation are established. Subsequently, simple vibrating models are derived from beams so as to consider the frequency characteristics of coupled vibration with tracks and vehicles. The results show that the difference of boundary conditions on rails changes the masses and springs contributing to vibration of the systems, changing the eigenvalues of vibration. These changes are reflected to the ABAs in such a way that a peak of resonant frequency of them gets lower when a vehicle running through broken rails. It is assumed that the rail breakage can be detected without wayside infrastructures by acquiring the ABAs and monitoring the change of them in the frequency domain.